PENGARUH JENIS FORMULA DAN TAKARAN PUPUK ORGANIK PLUS TERHADAP PERTUMBUHAN DAN PRODUKSI JAGUNG MANIS ( Zea mays saccharata Sturt) - Ariskun, Ariskun; Marlina, Neni; Syafrullah, Syafrullah (Klorofil: Jurnal Penelitian Ilmu-Ilmu Pertanian, 2017)
Effect of dose and the type Formula Plus Organic Fertilizer on the Growth and Production of Sweet Corn (Zea mays saccharata Sturt). This study aims to get the type and dose of organic fertilizer plus the right to the growth and production of sweet corn (Zea mays saccharata Strut). This research has been conducted on an experimental garden campus C Muhammadiyah University of Palembang, Semambu Island Village, North Inderalaya Subdistrict, Ogan Ilir, South Sumatra Province. This research has been going on from May to July 2015. This study uses a randomized block design (RAK) factorial combination with 15 treatments and 3 replicates with four plants examples. The factors following treatment. Type of organic fertilizer formula plus the following (F): F1 = Formula 1, F2 = Formula 2, F3 = Formula 3. The dose of organic fertilizer plus (T) as follows: T0 = 0 kg / ha. Control (chemical fertilizer recommendation sweet corn), T1 = 250 kg / ha, T2 = 500 kg / ha, T3 = 750 kg / ha, T4 = 100 kg / ha. Results of this study stated that the treatment of the type of formula 3 plus organic fertilizer with a dose of 1000 kg / ha, giving best on the growth and production of sweet corn crop at 4,50 kg / ha.